Prognostic impact of angiography-derived index of microcirculatory resistance in patients with dilated cardiomyopathy - Takayuki Kawamura; Koichiro Matsumura; Haruka Minami; Nobuhiro Yamada; Shohei Hakozaki; Yohei Funauchi; Naoko Soejima; Mana Okune; Kazuyoshi Kakehi; Masafumi Ueno; Gaku Nakazawa (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: Coronary microvascular dysfunction (CMD) has recently been associated with adverse cardiovascular events in patients with heart failure. We investigated the relationship between late gadolinium enhancement (LGE) and CMD, as well as the prognostic value of CMD in predicting long-term prognosis in patients with dilated cardiomyopathy (DCM). Methods: Patients with DCM who underwent both cardiac magnetic resonance imaging and coronary angiography were consecutively enrolled. CMD was evaluated using the angiography-derived index of microcirculatory resistance (angio-IMR). The primary endpoint was composite endpoints of all-cause mortality or heart failure hospitalization within 3 years. Results: Among 108 patients (median age, 64 years; women, 27 %), 18 % (19 patients) experienced composite endpoints. The median angio-IMR was 45 U, and LGE was identified in 23 %. Angio-IMR was significantly higher in patients with LGE than in those without LGE. When patients were stratified based on the combined presence of LGE and angio-IMR, significant differences in composite endpoints were observed among the three groups (LGE absence and low angio-IMR: 4.3 % vs. LGE presence or high angio-IMR: 22.2 % vs. LGE presence and high angio-IMR: 41.2 %, log-rank test p < 0.01). In multivariable Cox proportional hazards model for composite endpoints, LGE presence and angio-IMR >45 U was an independent predictor: hazards ratio 12.20, 95 % confidence interval 2.40–62.10, p = 0.001. Conclusion: CMD evaluated using angio-IMR was associated with LGE and long-term prognosis in patients with DCM. Further investigations are needed to elucidate the relationship among CMD, LGE, and prognosis.